(1)H-MR spectroscopy metabolite levels correlate with executive function in vascular cognitive impairment - Gasparovic, Charles (BMJ Publishing Group, 2013)
BACKGROUND: White matter hyperintensities (WMHs) are associated with vascular cognitive impairment (VCI) but fail to correlate with neuropsychological measures. As proton MR spectroscopy ((1)H-MRS) can identify ischaemic tissue, we hypothesised that MRS detectable brain metabolites would be superior to WMHs in predicting performance on neuropsychological tests. METHODS: 60 patients with suspected VCI underwent clinical, neuropsychological, MRI and CSF studies. They were diagnosed as having subcortical ischaemic vascular disease (SIVD), multiple infarcts, mixed dementia and leukoaraiosis. We measured brain metabolites in a white matter region above the lateral ventricles with (1)H-MRS and WMH volume in this region and throughout the brain. RESULTS: We found a significant correlation between both total creatine (Cr) and N-acetylaspartyl compounds (NAA) and standardised neuropsychological test scores. Cr levels in white matter correlated significantly with executive function (p=0.001), attention (p=0.03) and overall T score (p=0.007). When lesion volume was added as a covariate, NAA also showed a significant correlation with executive function (p=0.003) and overall T score (p=0.015). Furthermore, while metabolite levels also correlated with total white matter lesion volume, adjusting the Cr levels for lesion volume did not diminish the strength of the association between Cr levels and neuropsychological scores. The lowest metabolite levels and neuropsychological scores were found in the SIVD group. Finally, lesion volume alone did not correlate significantly with any neuropsychological test score. CONCLUSION: These results suggest that estimates of neurometabolite levels provide additional and useful information concerning cognitive function in VCI not obtainable by measurements of lesion load.